ABC's of Team Leadership in Emergency Medicine - Cullen Hegarty; Kelly Barringer; Jessie Nelson; Sharmila Raghunandan; Emily Binstadt (Association of American Medical Colleges, 2013)
Abstract Introduction Emergency medicine residents are required to direct major resuscitations during their training. However, residency programs vary greatly in preparing residents for this role with team leadership skills education. Thus, we sought to design a focused team leadership skills curriculum with dedicated feedback for residents leading both simulated and in situ resuscitations. Methods This resource includes an instructor's guide detailing all of the materials, a manuscript describing a literature review on team leadership (including a novel curriculum for team leadership training and self-evaluation), a copy of the self-evaluation form, and a PowerPoint presentation that features all of the key parts of the curriculum. Results We have used this curriculum at the Regions Hospital emergency medicine residency program for the past 2 years. Feedback indicates that the residents enjoy the simulation/lecture component and that the feedback form has been found to be user friendly and educational. Discussion One limitation of this resource is that it is specific to emergency medicine. However, the resource is easily transferable to other fields in medicine (e.g., surgery/trauma, medicine, pediatrics, etc.) as well.